Estimation of Bottom Friction Coefficient in Multi‐Constituent Tidal Models Using the Adjoint Method: Temporal Variations and Spatial Distributions. Issue 5 (29th April 2021) - Wang, Daosheng; Zhang, Jicai; Wang, Ya Ping
Abstract: The bottom friction coefficient (BFC) is critical for precisely determining hydrodynamic conditions and sediment transport rates, which are important for scientific research and coastal ocean engineering. The BFC varies spatially and temporally, as indicated by in situ observations, but it is difficult to accurately set this parameter in tidal models. In this study, based on a two‐dimensional multi‐constituent tidal model and its adjoint model, the harmonic constants of four principal tidal constituents ( M 2, S 2, K 1, and O 1 ) obtained from TOPEX/Poseidon altimeter data were assimilated to estimate spatially and temporally varying BFCs using the adjoint method in the Bohai, Yellow, and East China Seas. The model performance was significantly improved after data assimilation, which was independently tested by harmonic constants at coastal tidal gauge stations. Through several sensitivity experiments, the spatial distributions of the temporally averaged BFCs were verified to be robust and not affected by model settings, while the temporal variations of the spatially averaged BFCs were also robust but related to the tidal constituents. The variations in the estimated BFCs with the current speed and water depth were nearly consistent with those in the observations. Overall, the temporal and spatial variations in the estimated BFCs are significantly correlated with the current speed and water depth, which is attributed to the erosion‐deposition of sediment on the seabed and the changes in seabed roughness under different current speeds. The results can be beneficial for determining reasonable parameters for the bottom stress and setting the BFC in multi‐constituent tidal models. Plain Language Summary: Tides are a common phenomenon in the ocean and have a major impact on the design of coastal engineering projects and marine resource development. Numerical simulation is a valuable method for predicting tides, and the bottom friction coefficient (BFC) is the main model parameter of the tidal model. Generally, BFCs are spatially and temporally varying, causing difficulties in setting these parameters accurately in a tidal model. In this study, the spatially and temporally varying BFCs were estimated by assimilating satellite altimeter observations with the adjoint method to simulate the tides in the Bohai, Yellow, and East China Seas. The spatial distributions of the estimated BFCs do not change with the changing model settings, while the temporal variations of the estimated BFCs are affected by the number of simulated tidal constituents. The variations in the estimated BFCs are correlated with the current speed and water depth, and the possible reasons are analyzed. This study can be beneficial for determining reasonable parameters for the bottom stress and setting BFC in multi‐constituent tidal models. Key Points: Four principal tidal constituents were synchronously simulated by assimilating harmonic constants obtained from T/P altimeter data The spatially and temporally varying BFCs estimated using the adjoint method are nearly consistent with the observed BFCs BFC is correlated with current speed and water depth, which is attributed to the erosion–deposition of sediment and seabed roughness